Hypertensive Phase Following Silicone Plate Ahmed Glaucoma Valve Implantation. Issue 4 (April 2016) - Won, Hun Jae; Sung, Kyung Rim
Abstract : Purpose: To estimate the incidence of hypertensive phase (HP) following silicone plate Ahmed glaucoma valve implantation and to explore the risk factors for developing HP. Methods: A total of 325 eyes from 325 patients who underwent Ahmed glaucoma valve implantation for uncontrolled intraocular pressure (IOP) and were followed for at least 1 year were included. The HP was defined as IOP>21 mm Hg (with or without IOP-lowering medication) during the first 3 months after surgery. Eyes were divided into HP and non-HP development groups. Overall success was defined as reaching an IOP>5 and <22 mm Hg with (qualified success) or without (complete success) use of an IOP-lowering medication. Risk factors associated with HP development were determined by logistic regression analysis. Results: Among 325 eyes, 101 eyes (31.1%) experienced HP. For 24 eyes (23.8%), HP had not resolved by postoperative year 1. The HP group showed a significantly higher mean preoperative IOP than the non-HP group (37.1±11.4 vs. 32.3±11.2 mm Hg, P =0.004). The overall success rate was not significantly different between groups (81.2%, HP group vs. 89.7%, non-HP group; P =0.111); however, the complete success rate was significantly higher in the non-HP group (26.7% vs. 43.3%, P =0.003) at postoperative year 1. HP development was positively associated with preoperative IOP (odds ratio, 1.025; P =0.023). Conclusions: Higher preoperative IOP was associated with the HP development. The non-HP group achieved a higher complete success rate when assessed at postoperative year 1.